Awareness and Attitudes of Dental Students toward Older Adults in Indonesia - Anton Rahardjo; Fakhira Hanna Safira Firdaus; Peter Andreas; Yuniardini Septorini Wimardhani; Diah Ayu Maharani (MDPI AG, 2022)
In this study, we aimed to analyse the awareness and attitudes of dental students (DS) toward older adults (OAs) in Indonesia. Compromised oral health (OH) among OAs is a significant public health problem that is a global health burden. Furthermore, appropriate education can provide DS with information about strategic and efficient treatments for OAs. An online invitation was provided to every dental student in Indonesia in the third to sixth year of study to answer a web-based questionnaire as a part of a survey on awareness and attitudes (14 questions) towards OAs. From 1288 valid forms submitted, it was evident that most students (87%) expressed a positive attitude toward OAs. Female students showed a more positive attitude compared to males, with an odds ratio of 1.539 (p = 0.036), and students who had a connection to an older adult demonstrated a more positive attitude than those who did not (OR = 2.076; p < 0.001). The majority of the DS (98%) were conscious of the importance of geriatrics in dentistry, with female students showing more awareness than their male counterparts (OR = 2.553; p = 0.033). Positive awareness and attitudes must be accompanied by knowledge so that DS can offer appropriate and effective oral care to geriatric patients.